THE DOWNING OF MH17 IN UKRAINE: ANALYSIS FROM THE INTERNATIONAL LAW PERSPECTIVE - Alit Sudarsana, I Wayan; A. Martana, Nyoman (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 02, Mei 2015, 2015)
This paper discusses the horrible incident of MH17 which took place inUkraine. This paper uses the analytical approach method applied in legal research withthe aims of answering question presented in the paper. Beside the miseries faced by thefamily’s victims, the MH17 incident also bring us many international legal issues. Inthe end of the day, one of the three conclusion that could be drawn upon this paper isthatRussia could be held responsible for the incident under several circumstances.
Keywords: MH17, Responsibility, State, Jurisdiction